The search in designing Arabic typeface for a school of Arts and Design using User-Centered Design method - Al Qur'an, Hussam (Dirasat: Human and Social Sciences, 2021)
This qualitative study aims to explore the employing of the User-Centered Design method in the design process for a new Arabic typeface for a faculty of Art and Design. Where the study hypothesized that it is possible to create a typeface to be agreed upon by a target group of people, this can be achieved if using the User-Centered Design methodology. For testing this hypothesis, the Faculty of Arts and Design at the University of XX has been chosen to create its Arabic typeface, by organizing several rounds of Focus Groups among a study sample consisted of school students and faculty members who represent the target group. The study reached to design two typefaces for different uses instead of one, official and unofficial use. This study has proven its hypothesis, which suggests that it is possible to create a typeface that a target group of people can agree upon if employing the User-Centered Design method into the design process. Reliance in the typeface design processes on this method by engaging the end-users, and integrating them into the design stages, allows the designer and assists him in creating good and agreeable typeface, and therefore, achieves the goal for which it was designed.